Australia: the difficult birth of paid maternity leave - Brennan, D (The Policy Press, 2009)
This chapter looks at the issue of paid maternity leave in Australia. A focus on women as mothers, not workers, is deeply embedded in Australian culture and is reflected in this debate. There are many different views on maternity leave issues such as: should it be income replacement or social security payment; should employers contribute to the cost; eligibility requirements; benefits to non-working mothers. This chapter outlines the distinctive features of the Australian approach to social protection and industrial relations. It goes on to discuss some of the mechanisms Australia has adopted to meet its international obligations and describes current patterns of access to maternity and parental leave and other family income support. It then looks at the politics of the issue from the point of view of employers, unions, political parties and women's groups discussing the issue of paid maternity (and paternity) leave. The chapter concludes with an evaluation of possibilities for paid parental leave, with a postscript on the announcement of a government funded Paid Parental Leave (PPL) to begin January 1, 2011.
The Politics of Parental Leave Policies: Children, Parenting, Gender and the Labour Market
Keywords: Employment -- Parental leave; Policy; Employment; Labour market; Government, law and policy; Policy; Employment; Parental leave; Government, law and policy; Employment and unemployment